Protection or Vulnerability? A Meta‐Analysis of the Relations Between the Positive and Negative Components of Self‐Compassion and Psychopathology. (19th February 2016) - Muris, Peter; Petrocchi, Nicola
Abstract : Self‐compassion is increasingly explored as a protective factor in relation to psychopathology. The Self‐Compassion Scale (SCS) and its Short Form variant (SCS‐SF) are the most widely used instruments for measuring this psychological construct, and previous studies have indeed shown that the total score of this scale is negatively associated with psychopathology. In this article, we point out that half of the items of the SCS and SCS‐SF are positive indicators of self‐compassion and directly refer to the three key components of self‐kindness, common humanity and mindfulness, while the other half of the items are negative indicators of the construct and reflect the precise opposite of the key components, namely self‐judgment, isolation and over‐identification. A meta‐analysis was conducted including 18 studies that reported on the positive and negative indicators of self‐compassion as indexed by the SCS/SCS‐SF and their relations to various types of psychopathology. Results showed that positive indicators of self‐compassion were negatively associated with psychopathology, which confirms their hypothesized protective influence. However, the negative indicators were positively linked to psychopathology, suggesting that these scales tap increased vulnerability to mental health problems. Moreover, tests comparing the strength of the relations between various SCS/SCS‐SF counterparts (i.e., self‐kindness versus self‐judgment, common humanity versus isolation and mindfulness versus over‐identification) and psychopathology showed that the negative indicators were significantly stronger linked to mental health problems than the positive indicators. This provides support for the idea that the use of a total self‐compassion score of the SCS or SCS‐SF, which typically includes the reversely scored negative subscales, will probably result in an inflated relationship with symptoms of psychopathology. Copyright © 2016 John Wiley & Sons, Ltd.